Alger Hiss and the battle for history - Jacoby, Susan, 1945- (Icons of America., 2009)
Books on Whittaker Chambers and Alger Hiss abound, as countless scholars have labored to uncover the facts behind Chambers's shocking accusation before the House Committee on Un-American Activities in the summer of 1948, that Alger Hiss, a former rising star in the State Department, had been a Communist and engaged in espionage. In this work, the author turns her attention to the Hiss case, including his trial and imprisonment for perjury, as a mirror of shifting American political views and passions.